Modeling river runoff of literal tributaries of the Buktyrma reservoir with using HBV model (Journal of Geography and Environmental Management, 2023)
The article presents the results of applying the HBV-light model for 6 mountain rivers flowing into the Buktyrma reservoir: Buktyrma, Ulken Boken, Naryn, Kurshim, Turgysyn, Kalzhyr. Research work carried out the simulation of the flow of mountain river basins with a catchment area varying within 758-12423 km2. The parameters of the models were calibrated using the GAP optimization algorithm for the periods 1978-2017. The calibration period according to the recommendations for river basins were 5 years, with the exception of the Turgysyn and Kalzhyr river basins, where hydrological stations were opened in 2012 and 2007, respectively. For modeling the runoff as input hydrological and meteorological data were used data from the observation network of the RSE “Kazhydromet”. It should be noted that, due to the sparse network of meteorological stations, for Turgysyn, Kurshim, Ulken Boken, Naryn river basins as input data were used meteorological data from stations not located in the catchment areas of rivers. As a result of model calibration, the optimal parameters for each river are obtained. Several widely used criteria were used to evaluate the effectiveness of the model: NSW, PBIAS, RSR and R2. The results of calculations of these criteria correspond to a "very good" and "good" assessment of the performance rating: the Nash-Sutcliffe criterion varying between 0.84 – 0.92, the RSR ranges 0.32-0.45, the PBIAS -14.3 % to +18.2 %. According to the simulation results, it was revealed that the model for all the rivers under consideration reproduces the dates well the beginning, duration of the spring flood period and the maximum water consumption for this period. Given the sparse network of meteorological stations and the overregulation of some river basins, the using of the HBV-light model showed good results of modeling runoff for mountain rivers of Kazakhstan for calibration period. Also, the model was validated for 2018-2020 period. Validation results on performance criteria indicators for the Buktyrma and Ulken Boken river basins showed a “very good” replication result, while for the remaining 4 river basins the results were unsatisfactory, which was a consequence of management activities on the flow of river basins.
Keywords: water discharge, calibration parameters, model validation, Ertis water basin, digital elevation model.